PENGARUH RANSUM YANG BERBEDA PADA ITIK JANTAN TERHADAP JUMLAH LEUKOSIT DAN DIFERENSIAL LEUKOSIT - Bayu Eko Saputro; Rudy Sutrisna; Purnama Edy Santosa; Farida Fathul (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
This study aims to determine: 1) the number of leukocytes and the differential leukocyte drake by different rations; 2) the number of leukocytes and the differential leukocyte drake best with different ration. The research was conducted in September-December 2015 Integrated Laboratory, Faculty of Agriculture, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. This study uses a group design (RK). Grouping based on body weight with a weight range K1: 150-175 grams; K2: 176-200 grams; K3: 201-225 grams, and K4: 300-325 grams with level 4 treatments. Number of male ducks are used as many as 48 ducks males to 16 the number of plots so that each plot enclosure contains tigat male ducks. Data were collected at 10% of the number of ducks that exist in each treatment in each group. The data were analyzed by analysis of variance on the real level of 5% or 1% and continued with Duncan test for the value of the variance analysis showed significantly different results. The treatment is given in the form of rations drake 1, Ration 2 Ration 3 Ration 4 which has a different nutrient content so it can be the best diet to determine the level of normal leukocytes and leukocytes diferensial. The variables in this study are the leukocytes and the differential leukocytes include lymphocytes, monocytes, heterophile, eosinophils. The results showed that different ration was not significant (P> 0.05) and (P> 0.01) to the number of leukocytes and diferensial leukocytes. Keywords: Ducks Males, Leukocyte,  Rations